2009
DOI: 10.1098/rsif.2009.0020
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite coating of cellulose sponges attracts bone-marrow-derived stem cells in rat subcutaneous tissue

Abstract: The presence of bone-marrow-derived stem cells was investigated in a wound-healing model where subcutaneously implanted cellulose sponges were used to induce granulation tissue formation. When cellulose was coated with hydroxyapatite (HA), the sponges attracted circulating haemopoietic and mesenchymal progenitor cells more efficiently than uncoated cellulose. We hypothesized that the giant cells/macrophages of HA-coated sponges recognize HA as foreign material, phagocyte or hydrolyse it and release calcium ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
0
8
0
3
Order By: Relevance
“…540) shows to favor a faster bone repair, evident by micro CT analysis and by the formation of osteoid tissue. Previous studies have indeed shown that elevated Ca 2+ levels could promote the recruitment of bone marrow progenitor cells in vivo [26,27], regulate both bone morphogenetic protein and type I collagen synthesis by osteoblastic cells [28] and modulate the osteoinduction of mesenchymal stem cells [29]. Additionally, we and others have shown that bioactive glasses sustain the expression of proangiogenic cytokines and indirectly induce angiogenesis in vitro [25,30] and in vivo [10].…”
Section: Discussionmentioning
confidence: 65%
“…540) shows to favor a faster bone repair, evident by micro CT analysis and by the formation of osteoid tissue. Previous studies have indeed shown that elevated Ca 2+ levels could promote the recruitment of bone marrow progenitor cells in vivo [26,27], regulate both bone morphogenetic protein and type I collagen synthesis by osteoblastic cells [28] and modulate the osteoinduction of mesenchymal stem cells [29]. Additionally, we and others have shown that bioactive glasses sustain the expression of proangiogenic cytokines and indirectly induce angiogenesis in vitro [25,30] and in vivo [10].…”
Section: Discussionmentioning
confidence: 65%
“…However, despite its potential use as a biomedical scaffold, cellulose has not been widely applied in the eld of hard tissue regeneration owing to a loss of osteoconductivity. 19,20 To overcome the shortcoming of osteogenesis for pure cellulose, various composites using bioceramics (hydroxyapatite and calcium phosphate) have been accommodated. 21,22 In terms of structural formation, pure cellulose cannot be used to directly fabricate a 3D structure consisting of microstruts using a 3D printer because it is easily degraded or decomposed before melting takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue-specific CaSR deficient mice exhibit grave defects in bone and cartilage, highlighting the importance of this poorly studied receptor in many physiological processes (Chang et al, 2008). In vivo experiments indicate that bone marrow progenitor cells are mobilised to sites of high calcium concentration -such as calcium releasing biomaterials -possibly by CaSR-mediated chemotaxis, suggesting a role of these cells in high extracellular calcium environments like resorbing bone (Adams et al, 2006;Tommila et al, 2009).…”
Section: Introductionmentioning
confidence: 99%